EFEKTIVITAS FLIPPING STEM CLASSROOM TERHADAP PENINGKATAN KETERAMPILAN BERPIKIR KRITIS DAN PROFIL PERSEPSI KEMAMPUAN KOMUNIKASI SISWA PADA PEMBELAJARAN GELOMBANG BUNYI - Andreas Suparman, - (2023)
This study aims to determine the effectiveness of flipping STEM classrooms in improving critical thinking skills (CT) and the perception profile of students' communication skills. Flipping STEM classroom is a combination of flipped classroom and STEM approach focused on CT training and communication on sound wave material. As a comparison, flipped scientific classroom learning is applied to other classes on sound wave material. The method used is mixed methods, with an embedded experimental model design. Data on the increase in CT were obtained through the results of the pretest and posttest using an instrument in the form of a description question. While the profile data of students' perceptions of communication skills was obtained through the distribution of questionnaires at the end of the lesson. The increase in CT was analyzed using the normalized gain (n-gain) test, and learning effectiveness was analyzed using a hypothesis test using the t-test (independent sample t test), and the effect size calculation used the Cohen's d formulation, while the profile of students' communication skills perceptions was analyzed descriptively. The results showed that the increase in CT in the flipping STEM classroom learning was at a "high" level while in the flipped scientific classroom learning it was at a "medium" level. In addition, it was found that flipping STEM classroom learning was more effective for improving students' CT compared to flipped scientific classroom learning. In addition, the profile of perceptions of students' oral communication skills is at the level of "very good" and the profile of perceptions of students' written communication skills is at the level of "good".